Visualizing Global Energy Transition using Tableau - Punyisa Phumipho; Priyadarshini pattanaik; Sanchit Sarhadi (Universitas Komputer Indonesia, 2026)
The global transition to renewable energy presents both challenges and opportunities. This study uses data storytelling and Tableau’s visualization tools to explore energy trends from 2000 to 2019. Animated charts reveal rising renewable capacity and carbon emissions; notably, Brazil maintained low emissions despite economic growth. Geospatial analysis highlights China’s high emissions alongside rapid GDP growth, underscoring the vital need to balance development with sustainability (Mete, 2023). Furthermore, orbit charts expose regional gaps: Africa lags in wind and bioenergy, Asia leads in hydropower, and Europe excels in solar. These interconnected insights are crucial for policymakers to craft targeted strategies. Transforming complex data into visual stories supports informed decisions and drives innovative solutions toward a sustainable global energy future